FOREIGN MANUFACTURING INVESTMENT - DO AGGLOMERATION ECONOMIES MATTER? - Angels Pelegrin-Sole; Catalina Bolancé (European Regional Science Association (ERSA), 2005)
This paper examines the role that agglomeration economies play as location determinants in manufacturing foreign direct investment, with special emphasis on inter-industry heterogeneity. The analysis reveals that agglomeration economies are significant determinants of the regional distribution of manufacturing FDI, and that the nature and importance of locational determinants vary according to the specific needs of each industry. In short manufacturing agglomeration and location economies are the most important location factors, especially in industries with high level of linkages and in R&D intensive sectors.
Keywords: 330